Сравнительный анализ методов измерения джиттера - Костромицкий, А. И. (ХНУРЭ, 2009)
The given work is devoted to the classification of jitter, existing methods of measuring of the jitter, their pros and cons. The jitter is a very important parameter in the digital communication networks. The increase of the requirements for modem communication networks demands enhanced attention to this parameter.
Keywords: джиттер; анализ методов измерения джиттера